Student-Authored Publications as an Innovative Pedagogical Strategy to Enhance Course Learning Outcomes in Higher Education - Pranoto, Yohanes Heri (IJET (Indonesian Journal of English Teaching), 2026)
This study investigates the integration of student-authored publications as an innovative pedagogical strategy within Language Learning Assessment (LLA) and Second Language Acquisition (SLA) courses. Based on the Outcome-Based Education (OBE) framework and the MBKM (Merdeka Belajar–Kampus Merdeka) policy, this approach leverages student-authored publications as a means to deliver a more active, authentic, and performance-oriented learning experience. The study employed a qualitative descriptive method involving nine pre-service teachers. Data were collected through 16 weeks of classroom observations, a thematic analysis of 18 student-authored book chapters, and semi-structured interviews with two participants. The data were analyzed through thematic analysis. The results indicate that the publication project positively contributed to the achievement of Course Learning Outcomes (CLOs). This activity encouraged students to shift from simply understanding the material to actively synthesizing and constructing knowledge. In addition to improving academic achievement, the publication process also helped students establish their identities as pre-service teachers and scholars, strengthening their academic agency. However, students still face several challenges, particularly related to the high cognitive load and difficulty managing their time during the MBKM program. This project demonstrates strong alignment with the Impactful Campus spirit through its tangible contributions to society. Student-developed assessment resources were successfully utilized by partner schools, providing direct benefits to teaching practices. The study concludes that student-authored publications can serve as pedagogical bridges that meaningfully connect theory, practice, and reflection, provided they are supported by an adequate institutional framework.